Effects of Biostimulant Drugs on the Physiological State of Chicks - Shakhlo Babaeva, Ibragimova Feruza (American Journal of Bioscience and Clinical Integrity, 2025)
This study investigates the effects of biostimulant drugs on the physiological parameters of newly hatched chicks during the critical early developmental period. Biostimulants, widely recognized for their metabolic activation properties, are increasingly being used to improve poultry performance, particularly in intensive farming environments. The experiment assessed parameters such as body weight gain, feed conversion ratio (FCR), hematological indices, and immune responsiveness in chicks administered with different types and concentrations of biostimulants. Results showed a significant improvement in growth metrics and immune markers in the experimental groups compared to the control group. These findings suggest that biostimulants can positively influence the physiological state and overall productivity of poultry, offering a potential alternative to traditional growth promoters.